Entre désirs et tactiques : transactions intimes au sein de l’Entremise Matrimoniale Globalisée - Laure Sizaire (Genre & Histoire)
International matchmaking, which connects Western men and non-Western women, has been increasing since the 1990s and is particularly visible on the web. On the sites of international marriage agencies, intimate scenarios are developed and based on the staging of women’s bodies accompanied by sexist and essentialist discourses. It is these scenarios, and not the women, that are sold to clients as they objectify the women and thus fuel the fantasies of possession and masculine domination. This paper offers a reflection on the strategic use of intimacy on a global scale where money and sexuality are inseparable but if economic capital gives power to men, women’s sexuality is also constituted as a capital which can sometimes allow them to thwart male domination by drawing on their own weapons.